Association between gestational weight gain according to prepregnancy body mass index and short postpartum weight retention in postpartum women. Issue 2 (April 2015) - Ma, Defu; Szeto, Ignatius M.Y.; Yu, Kai; Ning, Yibing; Li, Wenjun; Wang, Junkuan; Zheng, Yingdong; Zhang, Yumei; Wang, Peiyu
Summary Background & aims This study aims to assess the relationship among prepregnancy body mass index, gestational weight gain, and postpartum weight retention, and to clarify the predictors of the amount of weight retained by Chinese women after pregnancy. Methods The multistage stratified random sampling was used in the cross-sectional study. Results The subjects included 1643 women. Mean gestational weight gain was 15.9 kg and mean postpartum weight retention was 5.1 kg. 43.2% of women gained excessive gestational weight gain and 53.3% of women gained 5 kg or more postpartum weight retention. In addition, the proportions of underweight women with inadequate weight gain and overweight women with excessive weight gain were 24.2% and 52.3%, respectively. Logistic regression analysis showed that the adjusted OR of excessive gestational weight gain was 1.74 (95% CI: 1.09–2.79) in overweight women compared with normal weight women. The postpartum weight retention and the proportion of women with postpartum weight retention of 5 kg or more were significantly higher in the excessive gestational weight gain women than in the adequate gestational weight gain women in all three body mass index groups. The adjusted OR of a weight increase of 5 kg or more was at least 1.90 for underweight, normal weight, and overweight women with a gestational weight gain above the recommended amount compared with those with a gestational weight gain within the recommended amount. Conclusions Gestational weight gain above the recommended amount increases the risk of postpartum weight retention in all body mass index groups.